Pola Komunikasi Orangtua dengan Remaja Adiksi Internet - Raharjo, Anggie Febriyanti; Sumardjijati, Sumardjijati (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The development of the digital era in the world is marked by new technology, namely the internet. Internet which is a facility that can be accessed by everyone around the world. The internet can not only be used for chatting and browsing, but in its development the internet can be increasingly widespread in its use. The existence of the internet is also felt by the people of Surabaya. The internet has a positive impact in the form of convenience for its users to access information with an online system that is easy, fast and affordable. Besides having a positive impact, the internet can also have a negative impact such as the occurrence of internet addiction, especially in teenagers. To prevent this from happening, good communication is needed between parents and children regarding the dangers of the internet so that addiction does not occur. This study uses a descriptive qualitative approach with an analysis of communication patterns according to Diana Baumrind. This data collection technique uses in-depth interviews with parents who have teenagers who experience internet addiction in the city of Surabaya. From the results of the study it can be concluded that parents apply permissive or liberating communication patterns, lack of interaction between parents and children and low supervision in internet use is the cause of children experiencing internet addiction. Keywords: communication patterns, internet addiction, Surabaya